Staff and patient perspectives of a smoke-free health services policy in South Australia: A state-wide implementation. Issue 8 (August 2017) - Martin, Kimberley; Dono, Joanne; Sharplin, Greg; Bowden, Jacqueline; Miller, Caroline
Highlights: Staff support for the smoke-free policy was high across all time points. Reports of witnessing some policy non-compliance were prevalent. One third of smoking patients were offered cessation support under the policy. Health-care staff should be further encouraged to offer support to nicotine-dependent patients. Abstract: Few jurisdictions have implemented and evaluated a complete smoking ban across all health sites in their jurisdiction, with no designated smoking areas. This article examines staff and patient perceptions and experiences of a mandated smoke-free policy implemented across all government health facilities in South Australia, including mental health sites. An online survey of health staff was conducted prior to policy implementation (n = 3098), 3 months post-implementation (n = 2673) and 15 months post-implementation (n = 2890). Consumer experiences of the policy were assessed via a telephone survey (n = 1722; smokers n = 254). Staff support for the policy was high across all time points. Two thirds of staff reported having witnessed some policy non-compliance, and self-reported exposure to second-hand smoke was comparable pre-implementation to 15 months post-implementation. Under the policy, 56.3% of smoking patients abstained completely whilst hospitalised and 37.6% cut down the amount that they smoked. Furthermore, 34.7% reported having been offered cessation support during hospitalisation. Whilst the smoke-free policy was viewed positively and had benefits for staff and patients, reports of witnessing some non-compliance were prevalent. While the extent of non-compliance is not known, and the measure used was sensitive, complementary strategies may be needed to reduce exposure to second-hand smoke, particularly at entrances. Health-care staff should be further encouraged to offer support to nicotine-dependent patients to foster compliance and promote abstinence during hospitalisation.